P‐101: Method of Accelerated Elemental Image Array Generation for Integral Imaging Display. Issue 1 (2nd June 2017) - Xing, Yan; Xiong, Zhao-Long; Deng, Huan; Wang, Qiong-Hua
Abstract : In this paper, we propose an accelerated elemental image array (EIA) generation method for integral imaging display. The EIA is directly generated by the calculated mapping matrices which are from original parallaxes to the EIA. We simplify the camera array calibration process, parallax alignment and interweaving processes into a simple remapping operation. The experimental results show that the proposed method can significantly accelerate the EIA generation.